From Third World to first the Singapore story, 1965-2000 - Kuan Yew, Lee (New York HarperCollins Publisher, 2000)
Few gave tiny Singapore much chance of survival when it was granted independence in 1965. How is it, then, that today the former British colonial trading post is a thriving Asian metropolis with not only the world's number one airline, best airport and busiest port of trade, but also the world's fourth highest per capita real income?
Includes Index
Keywords: Singapore-Economic Conditions